Carbon Dioxide Sequestration by Microbial Carbonic Anhydrases From Submarine Hydrothermal Systems - Ma, Xiaoyi; Liu, Le; Tang, Kai (Frontiers in Marine Science, 2022)
Owing to serious environmental and climatic impacts of increasing carbon dioxide (CO2) concentrations, there is an urgent need for the development of efficient CO2 capture methods. Carbonic anhydrases (CAs) can mediate CO2 capture via a rapid reaction between CO2 and bicarbonate ions. However, because of their stability, most of the CAs are not suitable for use in hostile environments (high temperature, high alkalinity, high pressure, and solvent). Therefore, this review explores thermophilic microorganisms in submarine hydrothermal environments as a valuable source of thermostable tolerant CAs, and highlights the questions and future directions that must be addressed for the application of CAs in CO2 capture.